Changing currencies and cognitive biases: evidence of the impact of introducing the Euro on dividend heaping in Europe. Issue 14 (22nd September 2021) - Jakob, Keith; Castillo, Augusto; Rubio, German
ABSTRACT: Heaping is defined as a cognitive bias to round numbers even if precise results are desired. This article targets on dividends in four key European markets (Germany, France, the UK, and Switzerland) over the 1981–2019 period. We hypothesize and report that the change of currency in Germany and France (they both adopted the Euro in January 1999) significantly influenced the characteristics of heaping observed in the dividends both in the short and in the long run. We also report that consistent with the prior literature, the probability of rounding of dividends in each country is significantly related to both information uncertainty and dividend size. In the UK and Switzerland heaping increases over time for the full 1981–2019 period for all designated rounding intervals. For Germany and France heaping increases for all rounding intervals during the 1981–1998 period, but the adoption of the Euro leads to a drastic reduction of heaping that lasts several years in both markets. In the long run, after the adoption of the Euro, the likelihood of heaping recovers for small rounding intervals, but remains well below the previous levels for larger rounding intervals.